Bonica's management of pain. - Fishman, Scott, 1959-; Ballantyne, Jane, 1948-; Rathmell, James P.; Bonica, John J., 1917-1994 (LWW medical book collection., 2010)
Now in its Fourth Edition, with a brand-new editorial team, Bonica's Management of Pain will be the leading textbook and clinical reference in the field of pain medicine. An international group of the foremost experts provides comprehensive, current, clinically oriented coverage of the entire field. The contributors describe contemporary clinical practice and summarize the evidence that guides clinical practice. Major sections cover basic considerations; economic, political, legal, and ethical considerations; evaluation of the patient with pain; specific painful conditions; methods for symptom.